High-pressure homogenization of olivine-hosted CO2-rich melt inclusions in a piston cylinder: insight into the volatile content of primary mantle melts - R. Buso; D. Laporte; F. Schiavi; N. Cluzel; C. Fonquernie (European Journal of Mineralogy, 2022)
Experimental homogenization of olivine-hosted melt inclusions representative of near-primary basic and ultrabasic magmas is a powerful approach to investigate the nature of their source regions and the melting conditions in Earth's mantle. There is growing evidence that the total CO2 contents of olivine-hosted melt inclusions may reach values of the order of a single to several weight percent, especially in intraplate continental basalts. To be able to homogenize melt inclusions with such high CO2 contents, we developed a technique allowing for heat treating of the melt inclusions under hydrostatic pressures up to 3–4 GPa in a piston cylinder, using thick-walled Au80–Pd20 containers and molten NaCl as the surrounding medium for the inclusion-bearing olivines. We applied this technique to olivine phenocrysts from Thueyts basanite, Bas-Vivarais volcanic province, French Massif Central. Thueyts melt inclusions were chosen because of their high CO2 contents, as indicated by up to 1.19 wt % dissolved CO2 in the glasses and by the presence of shrinkage bubbles containing abundant carbonate microcrystals in addition to a CO2 fluid phase. The homogenization experiments were conducted at pressures of 1.5 to 2.5 GPa, temperatures of 1275 and 1300 ∘C, and run durations of 30 min.